The Role of Tourism in The DevelopmeAnt of Regional Economy: Case Study of The Special Capital Region of Jakarta Province - Remi, Sutyastie Soemitro; Dwi Waluyo, SettingsSihono; Muljarijadi, Bagdja (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2017)
This study aims to assess the economic role of tourism to the economy of the Province of the Special Capital Region (DKI) of Jakarta. The research model used is the input-output model. The results showed that the tourism economy of Jakarta contributed significantly to the economy of Jakarta. The restaurant sector in the core sectors of tourism (hotel, restaurant, travel agency services and entertainment services, transportation) have the highest backward linkages and forward linkages as well as power distribution and a high level of sensitivity. In the tourist expenditure structure, the expenditure for sectors that are directly related to tourism highway transportation, hotel and restaurant occupy the highest role. Sectors that have an impact on the resulting output of the largest tourist expenditure is directly related to the sectors of tourism, namely the hotel sector, followed by the air transport sector, banks, insurance and business services, restaurant and travel agency services. While that get impacted gross value added is the largest hotel, air transport; banks, insurance and business services; restaurant and travel agency services. Which have an impact on wages / salaries is the largest hotel sector, air transport, restaurant and travel agency services. The impact of the tax, which obtained the largest sector was the hotel sector, followed by restaurants, trade and travel agency services. The resulting impact of labor is the hotel sector which obtained the largest share, followed by the restaurant sector, air transport and travel agency services. The results also show the potential for increased tourism to the economic value of Jakarta which can be achieved by: (1) prepare tourism policy related to trade, the bank sector, insurance and business services sector, the food industry, beverages, tobacco and cigarettes; the electricity sector / gas / water, and the construction sector, and (2) developing the core sectors of tourism with hotel sector priorities, the air transport sector, the sector of the restaurant, travel agency services sector, and the road transport sector. JEL Classification: H71, L80, L83Keywords: Input-Output, Labor, Linkages, Multipliers, Taxes, Wages/Salaries